In Vivo Microscopy Reveals Extensive Embedding of Capillaries within the Sarcolemma of Skeletal Muscle Fibers. (February 2014) - Glancy, Brian; Hsu, Li‐Yueh; Dao, Lam; Bakalar, Matthew; French, Stephanie; Chess, David J.; Taylor, Joni L.; Picard, Martin; Aponte, Angel; Daniels, Mathew P.; Esfahani, Shervin; Cushman, Samuel; et al.
Abstract Objective To provide insight into mitochondrial function in vivo, we evaluated the 3D spatial relationship between capillaries, mitochondria, and muscle fibers in live mice. Methods 3D volumes of in vivo murine TA muscles were imaged by MPM. Muscle fiber type, mitochondrial distribution, number of capillaries, and capillary‐to‐fiber contact were assessed. The role of Mb‐facilitated diffusion was examined in Mb KO mice. Distribution of GLUT4 was also evaluated in the context of the capillary and mitochondrial network. Results MPM revealed that 43.6 ± 3.3% of oxidative fiber capillaries had ≥50% of their circumference embedded in a groove in the sarcolemma, in vivo. Embedded capillaries were tightly associated with dense mitochondrial populations lateral to capillary grooves and nearly absent below the groove. Mitochondrial distribution, number of embedded capillaries, and capillary‐to‐fiber contact were proportional to fiber oxidative capacity and unaffected by Mb KO. GLUT4 did not preferentially localize to embedded capillaries. Conclusions Embedding capillaries in the sarcolemma may provide a regulatory mechanism to optimize delivery of oxygen to heterogeneous groups of muscle fibers. We hypothesize that mitochondria locate to PV regions due to myofibril voids created by embedded capillaries, not to enhance the delivery of oxygen to the mitochondria.